PERAN MAJELIS PENGAWAS DAERAH DALAM MENGAWASI NOTARIS DI KOTA MANADO - , ANDRE AMBROSIUS ABRAHAM PAAT; , Hariyanto, S.H., M.Kn ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Regional Supervisory Assembly is the supervisory institute of notary that have authority to oversee the notary profession, the purpose that in order to carry out his duties notary should according to provision of the regulations of notary position. This research aims to: (1) to find out the role of regional supervisory assembly in oversee the profession of notary in Manado. (2) to determine the constraints experienced by the regional supervisory assembly in order to oversee the profession of notary in Manado (3) to find out the efforts made by the regional supervisory assembly in overcoming the constraints in oversee the profession of notary in Manado. The characteristic of this research is juridical-empirical, which based on field research to obtain primary data and also conducted literature research in order to obtain secondary data. The subject of this research are respondent and informant who knows about the problem. Technique in determined the sample was purposive sampling and data analysis methods used are qualitative. Based on the research can be concluded that form of surveillance of the regional supervisory assembly towards the notary in Manado which can be carried out by conducting preventive supervision by inspecting the condition of the office and notary protocol, while the curative and guidance supervision cannot be carried out by the regional supervisory assembly of Manado, due to the constraints of limited time by members of regional supervisory assembly, restrictiveness of operational costs of regional supervisory assembly, the lack of knowledge in the notary field of the members of regional supervisory assembly and an inadequate of facilities. The efforts to overcome the constraints are by schedule meetings for the regional supervisory assembly in advance, using the personal expenses to support the implementation of surveillance, members of regional supervisory assembly from the notary should guide another member of regional supervisory assembly in order to provide a better understanding of notaryâs world.